2010
DOI: 10.3390/ma3031928
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Protein Drugs by Nanocarriers

Abstract: Recent advances in biotechnology demonstrate that peptides and proteins are the basis of a new generation of drugs. However, the transportation of protein drugs in the body is limited by their high molecular weight, which prevents the crossing of tissue barriers, and by their short lifetime due to immuno response and enzymatic degradation. Moreover, the ability to selectively deliver drugs to target organs, tissues or cells is a major challenge in the treatment of several human diseases, including cancer. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(106 citation statements)
references
References 266 publications
(274 reference statements)
1
102
0
3
Order By: Relevance
“…Therefore the optimal drug delivery system 100-200 nm are in the desired nanocarriers size range for tumor delivery, that is larger than the renal filtration cutoff and small enough for tumor penetration [32]. bilayers [14,19].…”
Section: Characterization Of the Dna-deposited Nanocapsules Loaded Bymentioning
confidence: 99%
“…Therefore the optimal drug delivery system 100-200 nm are in the desired nanocarriers size range for tumor delivery, that is larger than the renal filtration cutoff and small enough for tumor penetration [32]. bilayers [14,19].…”
Section: Characterization Of the Dna-deposited Nanocapsules Loaded Bymentioning
confidence: 99%
“…The problem with proteins, which limits its application in controlling cell functions, is the transportation of proteins into cells and the maintenance of their activity during the transportation. High molecular weight, hydrophilicity and easy degradation by enzymatic reactions can all inhibit this transportation [1][2][3]. Novel carriers for protein transportation are in development, and have been effective in maintaining protein activity, controlling the release rate, and reducing biological side effects [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies have shown that the use of nanocarriers, such as polymeric nanoparticles and liposomes, provides in vivo stability, prolonged circulation time, improved solubility, targeted release, and fewer side effects to peptide-protein drugs compared with conventional formulations. 3,6,9,10 Microspheres manufactured with natural and synthetic polymers have been studied as carriers for peptide-protein drugs because they protect the molecule during administration, regulate the blood levels, and exhibit a modified release that reduces repeated dosing. 5,[11][12][13] Finally, large, porous, biodegradable microspheres have been used as implant scaffolds in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the parenteral route (muscular or intravenous injection) is the most suitable one for administration. 5,6 In addition, the formulation techniques proposed, based on microencapsulation or freeze-drying, involve the use of organic solvents and interfaces that can provoke protein denaturation during microcarrier preparation. 7 For these reasons, routes that present a minimum of biological and technological drawbacks for these molecules have been suggested.…”
Section: Introductionmentioning
confidence: 99%